Women's work motivation in small and medium enterprises convection - Mochamad Mochklas; Indra Nur Fauzi; Hafidulloh Hafidulloh; Sofiah Nur Iradawaty (Institute of Computer Science (IOCS), 2023)
The existence of Small and Medium Enterprises has an important role in improving the welfare of the community, where convection is one of the SMEs that absorbs a lot of female workers. Human Resources is the main factor that drives the company, and work motivation is the drive to carry out work based on potential strengths originating in the workers. This study aims to describe the motivation of women who work in SMEs, where women also have a dual role as housewives who have jobs that are no less difficult to take care of the house and to work to increase income. The research method uses a quantitative descriptive approach, namely to describe, examine, and explain something that is studied as it is, and draw conclusions from the phenomena observed using numbers. The results of this study indicate that women who work in small and medium-sized convection SMEs have high school education, are of productive age and almost all of them are married. This condition causes women to accept jobs as they are in accordance with existing conditions, choosing jobs that are closer to home and working hours that are more flexible. The intrinsic motivation of women workers who work in this convection company is more dominantly perceived by the indicator of hope, and the extrinsic motivation of women workers who work in this convection company is more dominantly perceived by environmental indicators, namely the environment around the house